Tissue-on-a-Chip: Microphysiometry With Human 3D Models on Transwell Inserts - Schmidt, Christian; Markus, Jan; Kandarova, Helena; Wiest, Joachim (Frontiers in Bioengineering and Biotechnology, 2020)
Microphysiometry has proved to be a useful tool for monitoring the energy metabolism of living cells and their interactions with other cells. The technique has mainly been used for monitoring two-dimensional (2D) monolayers of cells. Recently, our group showed that it is also possible to monitor the extracellular acidification rate and transepithelial electrical resistance (TEER) of 3D skin constructs in an automated assay maintaining an air–liquid interface (ALI) with a BioChip extended by 3D-printed encapsulation. In this work, we present an optimized multichannel intestine-on-a-chip for monitoring the TEER of the commercially available 3D small intestinal tissue model (EpiIntestinalTM from MatTek). Experiments are performed for 1 day, during which a 60 min cycle is repeated periodically. Each cycle consists of three parts: (1) maintain ALI; (2) application of the measurement medium or test substance; and (3) the rinse cycle. A cytotoxic and barrier-disrupting benchmark chemical (0.2% sodium dodecyl sulfate) was applied after 8 h of initial equilibration. This caused time-dependent reduction of the TEER, which could not be observed with typical cytotoxicity measurement methods. This work represents a proof-of-principle of multichannel time-resolved TEER monitoring of a 3D intestine model using an automated ALI. Reconstructed human tissue combined with the Intelligent Mobile Lab for In vitro Diagnostic technology represents a promising research tool for use in toxicology, cellular metabolism studies, and drug absorption research.